Longitudinal Trends and Variation in Antipsychotic Use in Older Patients After Cardiac Surgery - Kim, Dae Hyun (J Am Geriatr Soc, 2018)
BACKGROUND: Despite lack of effectiveness and potential harms, antipsychotic medications (APMs) are often prescribed off-label for postoperative delirium. We evaluated the temporal trends and between-hospital variation of off-label APM use in older cardiac surgical patients. DESIGN: Retrospective cohort study. SETTING: A national administrative database including 465 United States hospitals. PARTICIPANTS: 293,212 patients ≥65 years, without known indications for APMs, who underwent cardiac surgery in 2004–2014. MEASUREMENTS: Postoperative exposure to any APMs and potentially excessive dosing was examined. The hospital-level APM prescribing intensity was defined as the proportion of patients newly treated with APMs in the postoperative period. RESULTS: The rate of APM use declined from 8.8% in 2004 to 6.2% in 2014 (p<0.001). Use of haloperidol (parenteral: 7.0% to 4.5%, p<0.001; oral: 1.9% to 0.5%, p<0.001) and risperidone (1.1% to 0.3%, p<0.001) declined, while quetiapine use tripled (0.6% to 1.9%, p=0.03). The hospital APM-prescribing intensity varied widely from 0.3% to 35.6% across 465 hospitals. Among the treated patients, those at higher prescribing hospitals were more likely to receive APMs on the day of discharge (highest vs lowest quintile: 15.1% vs 9.6%; p<0.001) and for a longer duration (4.8 vs 3.7 days; p<0.001). Delirium was the strongest risk factor for APM exposure (odds ratio, 9.73; 95% confidence interval, 9.02–10.5), whereas none of the hospital characteristics were significantly associated. The rate of potentially excessive dosing declined (60.7% to 44.9%, p<0.001) and the risk factors for potentially excessive dosing were similar to those for any APM exposure. CONCLUSIONS: Our findings suggest highly variable prescribing cultures and raise concerns about inappropriate use, highlighting the need for better evidence to guide APM prescribing in hospitalized older patients after cardiac surgery.